Influência da temperatura sobre a formação de biofilme e na expressão do oligopeptídeo permease de isolados de Pasteurella multocida de pulmões suínos - Kagueyama, Francielle Cristina (2017)
Pasteurella multocida is an important pathogen involving respiratory infections, such as atrophic rhinitis and swine pneumonia, with low temperatures and biofilm being important factors for the increase and chronicity of these infections, leading to great economic losses. The ABC transport system oligopeptide permease (opp) is an important nutritional virulence factor for the uptake of peptides, however in P. multocida there is no study related to this transport system. The objective of this study was to evaluate the influence of the low temperature on biofilm formation and the expression of opp in P. multocida isolated from pneumonic lesions of swine. Seven isolates of P. multocida were selected for the induction of biofilm formation in plates at 37 ° C and 25 ° C for 24 and 48 hours. The isolate Pm 16759 obtained higher biofilm formation at the 25 ° C condition for 24 hours, and approximately twice the biofilm production at the 37 ° C condition for 48 hours incubation. The transcript levels of oppA1 and oppA4 were overexpressed when subjected to low temperature (25°C) for 24 hours. Within 48 hours, oppA1 was repressed and oppA4 was three times more super expressed at 37°C. However, oppB, oppD and oppF showed levels of transcription similar to the reference of 37 ° C, but with repression at 25 °C. It is concluded that the temperature influences the formation of biofilm and the oppA1 and oppA4 genes overexpressed in this study, are regulated by the time of 24 hours and by the temperature of 25 °C, and may be associated with biofilm formation at low temperatures.